ANALISIS DAYA SAING USAHATANI KOPI ROBUSTA (Coffea canephora) DI KABUPATEN REJANG LEBONG - Murtiningrum, Fery; Asriani, Putri Suci; Badrudin, Redy (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
The research objectives are to 1) analyse the competitive advantage of robusta coffee farm in Rejang Lebong Regency, 2) analyse the comparative advantage of robusta coffee farm in Rejang Lebong Regency, 3) analyse the impact of government policy toward competitive robusta coffee in Rejang Lebong Regency, 4) analyse the sensitivity of competitive of robusta coffee toward the changing of input-output. The areas of the research are selected by purposive method. It considered that Rejang Lebong is one of regency in Bengkulu that is have been planted robusta coffee from one generation to others and makes coffee become superior commodity. Selecting sample is done by using stratified random sampling method. The sample is 32 respondents. The result analysis is using Policy Analysis Matrix (PAM). The research result shows that robusta coffee in Rejang Lebong has high competition (competitive advantage and comparative advantage). It is known that DRCR value is smaller than one, about 0,37 and 0,23. The impact of government policy toward input of the result analysis using PAM method is IT value is negative Rp.1.197.108/ha/year. Input Transfer (IT) value describes the policy (subsidy or tax) happened in tradable input production. IT value is negative for robusta coffee farm. It indicates that there is a policy subsidy toward tradable (anorganic fertilizer) input production in coffee farm. That is an advantage for coffee farmer. For output, IT value factor is positive 10.296. It indicates that there is a government policy toward domestic input such as tax. The input-output policy doesn’t work effectively or support or protect the coffee farmer in Rejang Lebong. The government policy is applied in coffee trade, so it causes coffee farmer doesn’t accept the price of coffee as social price. The sensitivity analysis result shows that robusta coffee farm has good competitive (competitive advantages and comparative). The factor assumption is constant with PCR and DRCR value less than one. Combination sensitivity analysis shows that input and output changing is caused by the decreasing of robusta coffee farmer competitive in Rejang Lebong. It is shown in competitive advantage with the PCR value more than one, about 2,43 and comparative advantage with DRCR value smaller than one, about 0,44.